A community for students.
Here's the question you clicked on:
 0 viewing
anonymous
 one year ago
Use a transformation to solve the equation.
d – (–17) = –14
A.
d = –31
B.
d = –3
C.
d = 3
D.
d = 31
anonymous
 one year ago
Use a transformation to solve the equation. d – (–17) = –14 A. d = –31 B. d = –3 C. d = 3 D. d = 31

This Question is Closed

AlexandervonHumboldt2
 one year ago
Best ResponseYou've already chosen the best response.0add to both sides 17

AlexandervonHumboldt2
 one year ago
Best ResponseYou've already chosen the best response.0you will get d(17)+(17)=14+(17 this is equal to d=1417=?

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0so the answer is 31?

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0@AlexandervonHumboldt2

whpalmer4
 one year ago
Best ResponseYou've already chosen the best response.0Put 31 in the original equation and check it to see! \[31  (17) = 14\] \[31 + 17 = 14\] \[31 +17  17 = 1417\] \[31 = 31\checkmark\] You have a true statement when you put the proposed answer in the original equation, therefore it is correct.

anonymous
 one year ago
Best ResponseYou've already chosen the best response.0oh, ok. thank you @whpalmer4 @AlexandervonHumboldt2
Ask your own question
Sign UpFind more explanations on OpenStudy
Your question is ready. Sign up for free to start getting answers.
spraguer
(Moderator)
5
→ View Detailed Profile
is replying to Can someone tell me what button the professor is hitting...
23
 Teamwork 19 Teammate
 Problem Solving 19 Hero
 Engagement 19 Mad Hatter
 You have blocked this person.
 ✔ You're a fan Checking fan status...
Thanks for being so helpful in mathematics. If you are getting quality help, make sure you spread the word about OpenStudy.